A Generalized Fabry–Pérot Formulation for Optical Modeling of Organic Light-Emitting Diodes Considering the Dipole Orientation and Light Polarization - Kyungnam Kang; Yongjeong Lee; Jungho Kim; Hyesog Lee; Byungchoon Yang (IEEE Photonics Journal, 2016)
The Fabry–Pérot formulation has been widely used as a simple and intuitive optical modeling method of organic light-emitting diodes (OLEDs). However, because the Fabry–Pérot formulation in the optical modeling of OLEDs does not include the effect of the dipole orientation and light polarization on light emission characteristics, rigorous electromagnetic models should be used, in spite of their heavy mathematical and computational complexity. In addition, the validity and the limitation of the Fabry–Pérot formulation for OLEDs have yet to be proven. We propose a generalized Fabry–Pérot formulation to calculate the dependence of the dipole orientation and light polarization on the angular emission characteristics using a simple analytical equation rather than a complicated electromagnetic model. The generalized Fabry–Pérot formulation is derived, together with detailed steps, and becomes equivalent to the current Fabry–Pérot formulation in isotropic dipole orientation. In addition, the physical interpretation of the proposed Fabry–Pérot formulation is elucidated in comparison with the quantum mechanical model. To demonstrate the applicability and the validity of the generalized Fabry–Pérot formulation, the angular emission spectra of a top-emitting OLED are calculated with respect to the horizontal dipole ratio and the light polarization, which can be easily calculated based on a simple analytical equation.